Case Report: Oleandrin intoxication by inhalation in beef cattle - Lisuzzo, Anastasia; Spadotto, Luca; Muraro, Michele; Mazzariol, Sandro; Centelleghe, Cinzia; Soranzo, Elena; Rubini, Silva; Locatelli, Carlo A.; Dacasto, Mauro; Taio, Giorgia; Fiore, Enrico; Gianesella, Matteo (Frontiers in Veterinary Science, 2025)
Oleander (Nerium oleander) contains more than 30 different toxic cardiac glycosides, including oleandrin. Intoxication can occur through ingestion or inhalation in several species, including cattle. A total of 76 of 205 beef cattle died within 30 h due to the burning of oleander mowing. The burning area was located approximately 20 meters from the animal housing facility. The clinical signs before death were depression, sternal decubitus, and dyspnea. Macroscopic examination revealed cavitary effusions, diffuse edema, and hemorrhagic changes. Histopathological examination confirmed hemorrhagic and edematous findings, minimal neutrophilic infiltration and hemorrhage in the heart, centrilobular hepatic necrosis, multifocal myopathy and necrosis, and chronic bronchitis. Oleandrin was detected in the lungs, kidneys, intracardiac clot, ruminal content, and liver. The concentration of oleandrin differed among tissues and animals, supporting the hypothesis that 74 of the 76 animals died from inhalation intoxication caused by oleander. The remaining two animals, which survived the hyperacute phase, later died due to secondary oleandrin intoxication via ingestion, which aggravated their pre-existing health conditions. To the best of the authors’ knowledge, this case represents the first reported instance of inhalation intoxication by oleander in cattle.